The thing (2011) [videorecording (DVD)] - Heijningen, Matthijs van, Jr., 1965-; Winstead, Mary Elizabeth; Edgerton, Joel, 1974-; Olsen, Eric Christian, 1977-; Campbell, John W., Jr. (John Wood), 1910-1971 (Universal Studios Home Entertainment, 2012)
When paleontologist Kate Lloyd travels to an isolated outpost in Antarctica for the expedition of a lifetime, she joins an international team that unearths a remarkable discovery. Their elation quickly turns to fear as they realize that their experiment has freed a mysterious being from its frozen prison. Paranoia spreads like an epidemic as a creature that can mimic anything it touches will pit human against human as it tries to survive and flourish in this spine-tingling thriller.